Impact of mindfulness dimensions on work engagement among white-collar employees during the new normal in Malaysia - Qing, Soh Ze; Singh, Jugindar Singh Kartar; Wern, Wong Huey (Journal of Social Economics Research, 2024)
This study examines the impact of mindfulness dimensions on work engagement among white-collar employees during the new normal in Malaysia. Employees today feel disengaged from their company in an environment where productivity and performance are critical. Research has indicated that elevated mindfulness levels have positive effects on the workplace and are a strong indicator of employee engagement. Previous studies have not thoroughly examined the impact of various facets of mindfulness on employee work engagement following the pandemic. This study investigated the impact of the four dimensions of mindfulness on employee engagement. This study was based on positivist philosophy and a deductive approach. Data for this quantitative study came from 227 employees in Malaysia's private sector who were employed in white-collar jobs. We gathered the primary data using a survey strategy and a self-administered questionnaire. The study's findings demonstrate a positive and significant relationship between work engagement and the four dimensions of mindfulness. More specifically, work engagement was most impacted by the mindfulness acceptance dimension, followed by the mindfulness awareness dimension. The study provided implications for both employers and employees regarding organizational programs aimed at enhancing mindfulness and work engagement, particularly in light of emerging work trends like remote work culture. This study expanded on the understanding of mindfulness at work for future researchers by looking at how mindfulness affects work engagement for white-collar workers and provided fresh insights, such as the greatest influence of the mindfulness-acceptance dimension.